Assessing Students' Readiness for Digital Learning in Higher Education - Dedy Aswan (Peneliti.net, 2026)
The increasing integration of digital technologies in higher education requires students to be adequately prepared for technology-enhanced learning environments. This study aimed to examine students’ readiness for digital learning in higher education. A quantitative descriptive survey was conducted involving 105 university students selected through convenience sampling. Data were collected using a 25-item questionnaire covering six dimensions: Technical Readiness, Self-Directed Learning Readiness, Communication Readiness, Motivation Readiness, Access Readiness, and AI/Digital Literacy Readiness. The instrument demonstrated good reliability with a Cronbach’s Alpha coefficient of 0.88. Data were analyzed using descriptive statistics, including mean and standard deviation. The findings revealed that students generally demonstrated a high level of digital learning readiness (M = 3.62, SD = 0.57). Technical Readiness and AI/Digital Literacy Readiness were categorized as high, while the remaining dimensions were at a moderate level. These findings suggest that although students possess strong technological competencies, improvements are needed in self-directed learning, communication, motivation, and access to digital resources.